Surface characterization of Ti-7.5Mo alloy modified by biomimetic method - Escada, A. L. A. [UNESP]; Rodrigues, D.; Machado, J. P. B.; Claro, A. P. R. Alves (Elsevier B.V. Sa, 2010)
Titanium and its alloys have been used in dentistry due to their excellent corrosion resistance and biocompatibility. It was shown that even a pure titanium metal and its alloys spontaneously form a bone-like apatite layer on their surfaces within a living body. The purpose of this work was to evaluate the growth of calcium phosphates at the surface of the experimental alloy Ti-7.5Mo. We produced ingots from pure titanium and molybdenum using an arc-melting furnace We then submitted these Ingots to heat treatment at 1100 degrees C for one hour, cooled the samples in water, and cold-worked the cooled material by swaging and machining. We measured the media roughness (Ra) with a roughness meter (1.3 and 2.6 mu m) and cut discs (13 mm in diameter and 4 mm in thickness) from each sample group. The samples were treated by biomimetic methods for 7 or 14 days to form an apatite coating on the surface. We then characterized the surfaces with an optical profilometer, a scanning electron microscope and contact angle measurements. The results of this study indicate that apatite can form on the surface of a Ti-7.5Mo alloy, and that a more complete apatite layer formed on the Ra = 2 6 mu m material. This Increased apatite formation resulted in a lower contact angle (C) 2010 Elsevier B.V. All rights reserved
Keywords: Titanium alloys; Surface roughness; Chemical treatment